Second year Latin. - Henle, Robert John, 1909 (Chicago : Loyola University Press, 1946)
"A sequel to first year Latin and ... intended to be accompanied by Latin grammar for high school."
Keywords: Latin language -- Composition and exercises; Latin language -- Chrestomathies and readers